2023
DOI: 10.3390/bs13010065
|View full text |Cite
|
Sign up to set email alerts
|

Both Sensorimotor Rhythm Neurofeedback and Self-Controlled Practice Enhance Motor Learning and Performance in Novice Golfers

Abstract: A major concern voiced by motor behavior scientists is to find useful practice techniques that can be effective in improving motor learning and performance. Neurofeedback and self-controlled practice are among the techniques that have recently drawn attention from specialists in this area. The present study examined the additive and individual effects of sensorimotor rhythm (SMR) neurofeedback as well as self-controlled practice on motor learning and performance in novice golfers. In this semi-empirical study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
6
1
Order By: Relevance
“…Furthermore, the results of these findings demonstrated that performing tasks with relatively low cognitive demands does not mean that SC is effective for motor learning. Although many preceding studies [5] [24] have argued that SC can be an significant intervention strategy to improve motor learning, judging from the results of this study, SC does not always improve motor learning. The ineffectiveness of SC in this study is considered to be due to the following reasons.…”
Section: Discussioncontrasting
confidence: 58%
“…Furthermore, the results of these findings demonstrated that performing tasks with relatively low cognitive demands does not mean that SC is effective for motor learning. Although many preceding studies [5] [24] have argued that SC can be an significant intervention strategy to improve motor learning, judging from the results of this study, SC does not always improve motor learning. The ineffectiveness of SC in this study is considered to be due to the following reasons.…”
Section: Discussioncontrasting
confidence: 58%
“…To further neurofeedback research in sports, future studies must rigorously investigate the most effective EEG markers, especially in the context of golf putting. Recent investigations, such as those conducted by Afrash et al (2023) and Pourbehbahani et al (2023), have underscored the benefits of enhanced sensorimotor rhythm (SMR) and suppressed alpha neurofeedback in facilitating long-term motor learning among novice golfers. Cheng et al (2015a) extended this research by correlating higher sensorimotor power at the Cz point with enhanced performance in skilled golfers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a decrease in frontal midline theta (FMT;(4)(5)(6)(7) power that is linked to sustained attention (Kao et al, 2014) can improve putting performance in skilled golfers (Chen et al, 2022b). In addition, increased sensorimotor rhythm (SMR; 12-15 Hz) power that is associated with attentional processing can improve putting performance in skilled golfers (Cheng et al, 2015a;Afrash et al, 2023) and novice golfers (Pourbehbahani et al, 2023). In addition to FMT and SMR, Mu rhythm can also modulate visuomotor performance.…”
Section: Introductionmentioning
confidence: 99%
“…Neurofeedback and self-controlled practice could achieve combined positive effects on performance and motor learning in novice golfers. Pourbehbahani and colleagues, in 2023, examined the individual and combined effects of sensorimotor rhythm (SMR) neurofeedback and self-controlled practice on motor performance learning in novice golfers [ 75 ]. For this study, the authors involved 40 athletes, divided into four groups: neurofeedback/self-controlled practice, neurofeedback/controlled practice, sham practice/self-controlled practice, and sham practice/controlled practice.…”
Section: Neurofeedback and Target-precision Sportsmentioning
confidence: 99%
“…The same authors conclude that self-controlled practice, which allows participants to make choices even not strictly related to the putting task, improves motor learning. This effect could be attributed to an increase in motivation, the possibility to experiment with different strategies, and control over personal choices [ 75 ]. Giving trainees the opportunity to make decisions can improve learning and motivation, even when the choices are not strictly related to the training content [ 76 ].…”
Section: Neurofeedback and Target-precision Sportsmentioning
confidence: 99%